The world's great thinkers, Vol.I-III - Commins, Saxe, Ed (Library has v1, v2 & v3, 1947)
[1] Man and spirit: the speculative philosophers. [2] Man and man: the social philosophers. Nicomachean ethics (Books I to V) / Aristotle; The Republic, Books II, Book VI / Plato; Apology / Plato; Crito / Plato; Principle doctrines / Epicurus; Fragments / Epicurus; The manual / Epictetus; Meditations (Books I to V) / Marcus Aurelius; The wisdom of Confucius / Confucius; The profit of one man is the loss of another / Michael de Montaigne; Of moderation / Michael de Montaigne; Of bad means employed to a good end / Michael de Montaigne; Cowardice, the mother of cruelty / Michael de Montaigne / Self-reliance / Ralph Waldo Emerson; The over-soul / Ralph Waldo Emerson; Compensation / Ralph Waldo Emerson; Morals and conduct / John Dewey. [3] Man and the state: the political philosophers. Of commonwealth / Thomas Hobbes; On civil government / John Locke; On liberty / John Stuart Mill; From the social contract / Jean Jacques Rousseau; Civil disobedience / Henry David Thoreau; From the wealth of nations / Adam Smith; Philosophical history / G.W.F. Hegel; The communist manifesto / Karl Marx. [4] Man and the universe: the philosophers of science. On the nature of things (Book V) / Lucretius; On the revolutions of the celestial spheres / Nicholas Copernicus; Novum Organum (Book I) / Francis Bacon; Discourse on method / René Descartes; The positive philosophy / Auguste Comte; Recapitulation and conclusion (from The origin of species) / Charles Darwin; The evolution of life (from Creative evolution) / Henri Bergson; The method of dream-interpretation / Sigmund Freud; Science and philosophy / Alfred North Whitehead; Some problems of philosophy / Sir James Jeans; Reality, causation, science and mysticism / Sir Arthur Stanley Eddington; The problems of space, ether and the field of physics / Albert Einstein.